2018
DOI: 10.3390/ijms19051428
|View full text |Cite
|
Sign up to set email alerts
|

Protein–Protein Interactions with Connexin 43: Regulation and Function

Abstract: Connexins are integral membrane building blocks that form gap junctions, enabling direct cytoplasmic exchange of ions and low-molecular-mass metabolites between adjacent cells. In the heart, gap junctions mediate the propagation of cardiac action potentials and the maintenance of a regular beating rhythm. A number of connexin interacting proteins have been described and are known gap junction regulators either through direct effects (e.g., kinases) or the formation of larger multifunctional complexes (e.g., cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 180 publications
(187 reference statements)
0
64
0
Order By: Relevance
“…We speculate that the interaction between Cx43 junctional complex and tight junction ZO proteins, or with molecules like Par3 that are involved in the PI3K-AKT pathway controlling MSO (Tenvooren et al, 2019), might underlie Cx43mediated MSO. It is unlikely that Cx43 exerts an impact on MSO via its known interaction with tubulin (Sorgen et al, 2018;Vanderpuye et al, 2016), since we rarely observed Cx43 localized near the mitotic spindle (Fig. S6C).…”
Section: Cx43 Controls the Direction Of Cell Divisionmentioning
confidence: 92%
“…We speculate that the interaction between Cx43 junctional complex and tight junction ZO proteins, or with molecules like Par3 that are involved in the PI3K-AKT pathway controlling MSO (Tenvooren et al, 2019), might underlie Cx43mediated MSO. It is unlikely that Cx43 exerts an impact on MSO via its known interaction with tubulin (Sorgen et al, 2018;Vanderpuye et al, 2016), since we rarely observed Cx43 localized near the mitotic spindle (Fig. S6C).…”
Section: Cx43 Controls the Direction Of Cell Divisionmentioning
confidence: 92%
“…Moreover, connexin-based channels at the plasma membrane that are not assembled into gap junctions, also known as hemichannels, have central roles in autocrine and paracrine signaling by providing a pathway for the exchange of ions and small molecules between the intracellular and extracellular milieus [7]. In addition, the intracellular domains of connexins can interact with other proteins, including components of the cytoskeleton, such as tubulin, and cell signaling pathways, such as cyclin E and β-catenin [8][9][10][11]. Through such protein-protein interactions, connexins can modulate cell growth, differentiation, migration and other cellular processes in channel-independent manners.…”
Section: Introductionmentioning
confidence: 99%
“…induces its degradation, and these results suggest that SGSM3 may induce Cx43 turnover through the lysosomal pathway [34]. The Cx43 is affected by interactions between Cx43 and numerous proteins, which related to trafficking, channel construction, and degradation [35,36]. SGSM3 increases Cx43 turnover by accelerating the internalization of Cx43 from the plasma membrane [37].…”
Section: Plos Onementioning
confidence: 90%